Etnolamp: Integrating Lampung Ethnomathematics into Articulate Storyline for Contextual SPLDV Learning - Selvi Loviana; Sugeng Sutiarso; Farida Ariyani; Sowiyah Sowiyah; Nurhanurawati Nurhanurawati (CV FOUNDAE, 2026)
Integrating local cultural knowledge into digital mathematics learning remains underexplored despite growing interest in culturally responsive education. This study developed and evaluated **Etnolamp**, an interactive ethnomathematics learning environment that combines Lampung cultural contexts with Articulate Storyline to support contextual learning of Systems of Linear Equations in Two Variables (SPLDV). The study employed a research and development approach adapted from the Borg and Gall model, encompassing needs analysis, product design, expert validation, revision, and limited classroom implementation involving 16 ninth-grade students in Indonesia. Data were collected through interviews, expert validation instruments, and student response questionnaires to evaluate the product’s validity and practicality. The findings indicate that Etnolamp achieved high expert validation and was perceived by students as a practical and engaging learning resource. By integrating instructional materials, interactive videos, contextual exercises, educational games, and culturally relevant mathematical problems into a single digital platform, the media promoted meaningful connections between abstract algebraic concepts and students’ everyday cultural experiences. This study contributes a culturally responsive multimedia design framework that demonstrates how ethnomathematics and interactive digital technologies can be integrated to support contextual mathematics learning, providing a foundation for future investigations into its effectiveness in improving mathematical understanding and problem-solving